2019
DOI: 10.1002/jctb.6131
|View full text |Cite
|
Sign up to set email alerts
|

Waste products from the poultry industry: a source of high‐value dietary supplements

Abstract: BACKGROUND The production and consumption of chicken has doubled in the last 17 years. Since slaughter yields range from 70 to 80%, during production various chicken waste residues are generated. One of these residues is waste created after the mechanical separation of chicken meat (W‐MSM). The goal of the circular economy is to manage this waste and transform it into a valuable product. RESULTS W‐MSM was subjected to hydrolysis by the proteolytic enzymes pepsin and papain to obtain bioactive compounds. Papain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…The results of protein and peptide analyses (Stiborova et al 2020) of the pilot and operational hydrolysates showed that a significantly higher amount was found in the hydrolysate prepared in the operational reactor, namely 36.9 g/L as distinct from 23.3 g/L in the pilot hydrolysate; see Table 2. Probably, an essential role was played by the reaction time; 16 h compared to 5 h.…”
Section: Process Scale-upmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of protein and peptide analyses (Stiborova et al 2020) of the pilot and operational hydrolysates showed that a significantly higher amount was found in the hydrolysate prepared in the operational reactor, namely 36.9 g/L as distinct from 23.3 g/L in the pilot hydrolysate; see Table 2. Probably, an essential role was played by the reaction time; 16 h compared to 5 h.…”
Section: Process Scale-upmentioning
confidence: 97%
“…The composition of the hydrolysate (Stiborova et al 2020), such as the proportion of the individual amino acids, the amount of peptides and proteins, the elemental composition belongs to the most important characteristics of the hydrolysate. Proportions of the individual amino acids for laboratory, pilot and operational reactors are shown in Fig.…”
Section: Process Scale-upmentioning
confidence: 99%
“…The results of protein and peptide analyses (Stiborova et al 2020) of the pilot and operational hydrolysates showed that a signi cantly higher amount was found in the hydrolysate prepared in the operational reactor, namely 36.9 g/L as distinct from 23.3 g/L in the pilot hydrolysate; see Table 2.…”
Section: Process Scale-upmentioning
confidence: 98%
“…The composition of the hydrolysate (Stiborova et al 2020), such as the proportion of the individual amino acids, the amount of peptides and proteins, the elemental composition, etc., belongs to the most important characteristics of the hydrolysate.…”
Section: Process Scale-upmentioning
confidence: 99%
“…In the same line, Stiborova et al evaluated the waste products from poultry industry as possible source of high-value dietary supplements. 11 These particular materials through hydrolysis with papain and further processing can generate final products with bioactive ingredients like hyaluronic acid (HA), chondroitin sulfate (CS), peptides and amino acids. This process is a representative transformation of by-product emphasizing on the value of circular economy.…”
mentioning
confidence: 99%